Correlation analysis between physicians' evaluations of doctor–patient relationship and their preferences for shared decision-making in China - Zhuo-Ran Chen; Li Zhang; Ya-Wei Chen; Meng-Yang Xu; Hang Jia; Meng-Ying Li; Yu-Han Lou; Yu-Han Lou; Yu-Han Lou; Ling Lan; Ling Lan; Ling Lan (Frontiers in Psychiatry, 2022)
Shared decision-making (SDM) is a scientific and reasonable decision-making model. However, whether physicians choose SDM is usually influenced by many factors. It is not clear whether the strained doctor–patient relationship will affect physicians' willingness to choose SDM. Through a survey by questionnaire, 304 physicians' evaluations of doctor–patient relationship (DPR) were quantified by the difficult DPR questionnaire-8. Their preferences for SDM and the reasons were also evaluated. The correlation between physicians' evaluations of DPR and their preferences for SDM were analyzed. 84.5% physicians perceived DPR as poor or strained, 53.3% physicians preferred SDM, mainly because of the influences of medical ethics and social desirability bias. Their preferences for SDM were not significantly correlated with their evaluations of DPR (P > 0.05). Physicians with different evaluations of DPR (good, poor, and strained) all had similar preferences for SDM (42.6, 56.4, and 42.9%), with no significant difference (P > 0.05). There was no correlation between physicians' evaluations of DPR and their preferences for SDM. Physicians' evaluations of poor DPR did not affect their preferences for SDM. This may be influenced by the medical ethics and social desirability bias.